Mātauranga and Science II – Introduction - Jackson, Anne-Marie; Mercier, Ocean (New Zealand Science Review, 2020)
Haere mai te ihi haere mai te wehi, haere mai te mana, haere mai te tapu.‘ Draw near o excellent ones, draw near o awesome ones, draw near o charismatic ones, draw near o sacred ones’ (Marsden, 2003, p. 3) This second edition offers additional definitions and examples of mātauranga and science in practice, and advances the basis of such scholarship, across a range of contexts. The papers highlight the relevance, innovation, and dynamism of mātauranga. It questions the taken-for-granted assumptions of scientific thought which are deeply entrenched in modern society and rather encourage us to seek ‘a passionate, inward subjective approach’ (Marsden, 2003, p. 22–23) as perhaps ‘abstract rational thought and empirical methods cannot grasp the concrete act of existing which is fragmentary, paradoxical and incomplete’ (Marsden, 2003, p. 22–23). The contributing authors reflect the breadth of experiences in mātauranga and the need for research that is written by those knowledge holders and practitioners of mātauranga. This Special Issue offers a hopefulness to Smith’s (1999) caution that, too often, Māori and indigenous peoples were the subject of study as the ‘other’. This caution was seen too frequently in scientific study historically, but sadly, still occurs today, at societal, systemic, political, community, and individual levels. Yet, despite these circumstances, we are reminded of a whakatauākī a prominent chief to Ngāti Whātua¹, Ihenga uttered in the context of an ongoing battle: Me whakapakari ki te hua o te kawariki ‘Leave us and we will mature like the fruit of the kawariki’ This is an oft-heard remark at marae in Ngāti Whātua referring to the ongoing strength of our whānau as, like the resilient kawariki, a plant that can survive and flourish in an ever changing environment.